Islamic Religiosity as A Moderator of The Effect of Organizational Climate on Happiness at Work in Islamic School Teachers - Delya, Ananda Krisma; Naimah, Tri; Wibowo, Ugung Dwi Ario; Wahidah, Fatin Rohmah Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to determine the organizational climate's effect on work happiness with Islamic religiosity as a moderator variable for Islamic-based school teachers in the Banyumas Regency. A correlational quantitative approach was used for this study. Respondents in this study were 86 permanent teachers. Data collection uses the happiness at organizational ClimateCare and Islamic religious scale. The data analysis technique used tests the outer and inner models with the SmartPLS 3.0 tool. The research findings show that organizational climate and Islamic religiosity have a significant effect on happiness at work. However, the moderator test shows no significant effect between organizational climate and happiness at work when Islamic religiosity functions as a moderator variable. The recommendation from the research is that to increase happiness in the workplace needs to pay attention to personal and organizational factors. Although Islamic religiosity does not moderate the relationship between organizational climate and happiness at work, further research can be conducted to gain a deeper understanding of other variables that function as moderators.